2023
DOI: 10.1007/s10965-023-03795-3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the thermal stability of α-diimine nickel (II) catalyst by camphorquinone as a great backbone and investigating the steric effects of this backbone in ethylene polymerization

Zahra Issaabadi,
Hassan Arabi,
Majid Karimi

Abstract: In the α-diimine catalyst system, catalyst design with high thermal stability through ligand modifications is very challenging. This paper reports the preparation of three camphyl-based ligands with diverse steric effect and their Ni (II) complexes. To evaluate the backbone and ligand steric effects these nickel complexes were used as catalysts in the polymerization of ethylene. The camphyl-based catalysts show high thermal stability with good catalyst activity up to 75 °C. In ethylene polymerization using bul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…5,6 Furthermore, multisite catalysts still have limited potential for implementation in commercial processes. [7][8][9] Sturzel et al applied three-site catalysts supported on functionalized graphene to achieve self-reinforced polyethylene with trimodal molar mass distributions, so that trimodal product had both great stiffness and high impact strength. 10 Shijie Song et al explored the rheological and mechanical properties of melt-compounded bimodal HDPE with a small loading of UHMW polyethylene and found that meltblended trimodal HDPE exhibited exceptional melt strength and processability.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Furthermore, multisite catalysts still have limited potential for implementation in commercial processes. [7][8][9] Sturzel et al applied three-site catalysts supported on functionalized graphene to achieve self-reinforced polyethylene with trimodal molar mass distributions, so that trimodal product had both great stiffness and high impact strength. 10 Shijie Song et al explored the rheological and mechanical properties of melt-compounded bimodal HDPE with a small loading of UHMW polyethylene and found that meltblended trimodal HDPE exhibited exceptional melt strength and processability.…”
Section: Introductionmentioning
confidence: 99%